Adult Education for a Civil Society: Starting Over - Pramila Aggarwal; Bill Fallis; Bob Luker (Adult Education Research Conference, 2000)
To "start over" adult educators need to reexamine the present practice of adult education and community development in Canada, as compared to our earlier ideals for the field that included the promotion of greater democracy, social equality and equitable economic opportunities for all Canadians. In this reassessment, we need to consider the broader potential of our community agencies, as sites for revitalizing our civil society.